Qualitative Study on Physicians' Motivations and Drug Prescribing Behaviour - Luminita Mihaela Ion (CES Working Papers, 2013)
The proper prescription of medicines by specialists from healthcare, especially physicians, it's a major challenge of the healthcare services concerning the financial implications respectively the effects upon the patient's health status. The assurance of a proper and adequate prescription for the patients is influenced by a series of factors which act upon the prescription decision of the medicines, as: the medicine features (quality-price, availability), the patient's situation, the prescriber, respectively the professional environment. The estimate of a physician behaviour concerning the action of prescribing to the patients leads to the discovery of the major role that the intention has on the behaviour. The present study aims at carrying out a thorough research on drug prescribing behaviour to patients, trying to identify the motivations which underlie the action of prescribing.
Keywords: M14; M19; M39; I11; I13; I19; 330; patients; factors; drug prescribing behaviour to patients Romania